Atomistic Insights into Interfacial Optimization Mechanism for Achieving Ultralow-Friction Amorphous Carbon Films under Solid-Liquid Composite Conditions - Du, Naizhou; Li, Xiaowei; Wei, Xubing; Chen, Zan; Lu, Shiqi; Ding, Jiaqing; Feng, Cunao; Chen, Kai; Qiao, Jianghao; Zhang, Dekun; Lee, Kwang-Ryeol (American Chemical Society, 2023)
The combination of fluid lubricants and textured amorphous carbon (a-C) can provide an ultralow friction state, which can improve the reliability and service life of dynamic machinery. However, the coupling effects of the contact pressure and oil content on the friction-reducing efficiency is still lack of study, and the corresponding friction mechanism is also not fully understood, which cannot be achieved by experiment due to the limitation of in situ characterization. In this study, using the reactive molecular dynamics simulation, the insight into the evolution of interfacial structures induced by both contact pressures and oil contents on a-C surface was systematically investigated to explore the fundamental mechanism. In particular, the friction difference between textured and untextured a-C films was evaluated comparatively. Results indicate that the tribological performance strongly depends on the interfacial lubrication state, which is jointly determined by the oil content and contact pressure; the best operating condition to achieve ultralow friction coefficient (0.002) is obtained, and the evolution of friction coefficient with oil content and contact pressure is highly dominated by the lubricant mobility, cross-linking between mating a-C surfaces, or competition/synergy of the H stress state from the lubricant with interfacial passivation. Furthermore, the difference in friction reduction between textured and untextured systems is unveiled; with the increase of contact pressure, the role of texturing a-C surface in antifriction changes from positive to negative effect, which is related to the transformation of interfacial hybridized structure and anomalous flow of lubricant. These results can significantly enhance the understanding of composite lubrication systems through computation and also provide a roadmap for the R&D of the advanced lubrication system according to the working conditions.